Immune Thrombocytopenia: Characteristics of the Population and Treatment Methods—One-Center Experience - Lebowa, Weronika; Zdziarska, Joanna; Sacha, Tomasz (Hämostaseologie, 2022)
Background Immune thrombocytopenia (ITP) is a disease with variable clinical presentation, requiring different treatment lines.Aim The study aimed to characterize a group of ITP patients in terms of clinical picture and disease treatment, as well as to present the current standard of care of ITP in Poland, in the context of local and international guidelines.Materials and Methods The study included adult patients diagnosed with ITP, treated at the Department of Haematology of the Jagiellonian University Hospital in Krakow from January 2006 to January 2021. Patient characteristics, clinical manifestation of ITP, and treatment methods were analyzed.Results A total of 245 ITP patients were included. 57.1% of them were asymptomatic at diagnosis. Most common symptoms were thrombocytopenic purpura (68.2%), followed by epistaxis (34.7%) and gum bleeds (19.2%). Life-threatening bleedings were noted in three cases (1.2%). 23.2% of patients did not require treatment. Prednisone was the most commonly used first-line therapy (75.5% of patients). Treatment with eltrombopag and romiplostim was used in 40.4 and 8.5% of patients requiring second-line therapy, respectively. 14.3% of all patients ultimately underwent splenectomy, including 51.5% of those who needed second-line treatment. The initial response rate was 74.3%; however, post-splenectomy relapses occurred in 22.9% of patients.Conclusions ITP is a disease of mild clinical course, often asymptomatic. Chronic disease often requires multiple treatment lines and balancing between bleeding risk and treatment toxicity, based on individual risk–benefit assessment. Local access restrictions to thrombopoietin receptor agonists determined the treatment strategy.
Keywords: immune thrombocytopenia; refractory ITP; splenectomy; thrombopoietin receptor agonists